ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PENERIMAAN RETRIBUSI PASAR KABUPATEN KOTA PROVINSI SUMATERA BARAT - Syaza Nuri Mahera; Zul Azhar; Mike Triani (Universitas Negeri Padang, 2018)
This research is aims to analyze the effect of Economic Growth and the number of poducers toward revenue of retribution in seven regencies in West Sumatra. Method that being used is Panel Least Square and is used Random Effect Model (REM). Data used is panel data from 2012-2016 from Badan Pusat Statistik, Badan Kuangan Sumatra Barat, and DJPK Indonesia. The estimation results show that Economic growth has a positive and significant effect on retribution and Sellers has a positive and significant effect on retribution. This result shows that economic growth and sellers has partial effect to revenue of retribution. This study is to give information about govenrment income specially retribution and government could increase service facility of market to achieved revenue target from retribution.